Optimizing organic resource allocation to enhance microbial necromass nitrogen accrual: Evidence from multiple long-term fertilization experiments - Jun Wang; Yaping Huang; Qiong Xiao; Dong Wu; Dongchu Li; Xin Li; Lei Wu; Yinghua Duan; Minggang Xu; Wenju Zhang (Agriculture, Ecosystems & Environment, 2026)

Chemical constituents from the aerial parts of Rauvolfia yunnanensis Tsiang and their chemotaxonomic significance - Wanqi Yang; Xiaoyan Cui; Renfeng Ye; Min Jiang; Shijing Tang; Wenjing Dong; Guiguang Cheng; Yaping Liu (Biochemical Systematics and Ecology, 2026)

Sub-chronic copper exposure alters growth performance, intestinal histopathology, and intestinal microbiota in adult zebrafish (Danio rerio) - Yaping Wang; Yaqian Fu; Xuyang Zhai; Chang Dong; Mengdie Yang; Ziyi Huang; Fei Liu (Ecotoxicology, 2026)

Integrative metabolomic and genomic characterization of the high antimicrobial activity of Lacticaseibacillus paracasei and its potential for juice preservation - Fu Wei; Yanmei Sun; Yaping Mi; Chen Liang; Meichi Yue; Kehui Zhang; Rui Dong; Ziyi Zhang; Qiannan Yang; Songtao Guo; Shiwei Wang (Food Research International, 2026)

Bisphenol A exposure disrupts the circadian clock system and impairs glycolipid metabolic function in mice liver - Hao Dong; Wenli Ding; Bonan Xiao; Cuimei Li; Haizhen Jiang; Wanghao Yang; Dan Li; Chao Li; Haisen Zhang; Dengke Gao; Aihua Wang; Yaping Jin; et al. (Food and Chemical Toxicology, 2026)

Coupling near infrared spectroscopy with machine learning algorithms for simultaneously detecting multiple microplastics in soil - Jia Long; Xi Li; Renjie Yang; Guimei Dong; Yaping Yu; Huiyong Shan (Journal of Soils and Sediments, 2026)

Large-scale farming enhances soil health in contrast to smallholder management: Insights from a field survey - Xin LI; Dong WU; Yaping HUANG; Xiao YANG; Gilles COLINET; Caroline DE CLERCK; Wenju ZHANG; Minggang XU; Jeroen MEERSMANS (Pedosphere, 2026)

Tuning CO2 separation of Type I UiO-66 porous liquids by varying the size of porous hosts - Shuangshuang Long; Jingwen Wang; Shuqian Meng; Yaxin Liu; Jing Zhang; Zihao Ren; Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Libing Qian; Wenwu Zhou; et al. (Journal of Environmental Chemical Engineering, 2026)

N, S-co-doped carbon quantum dots as a versatile platform for monitoring hydrogen sulfide and nitrite based on Fe2+/Fe3+ redox cycle: Applications in food safety and bioimaging - Yaping Zhong; Kayi Shao; Ruixia Zhang; Linlong Zhang; Dong Wang (Food Control, 2026)

Characterization of T5DL·5DS-2RS, a wheat-rye chromosomal translocation with enhanced grain hardness and pre-harvest sprouting resistance - Xin Liu; Huiting Zhang; Zhenglan Cao; Yanhong Lei; Mengyu Han; LiBin Wang; Yilong Dong; Jishan Niu; Yaping Cao; Jiajia Zhao; Jun Zheng; Xueming Yang; et al. (Theoretical and Applied Genetics, 2026)

(P)ppGpp synthase Rsh promotes persister cells formation by regulating sulfur metabolism mediated by sulfate reductase CysI in Brucella abortus - Xiaofang Liu; Chenyang Cui; Pingping Wang; Hui Wang; Yunyi Zhai; Yuanhao Yang; Jialu Chen; Wei Liu; Zheng Dong; Dong Zhou; Yaping Jin; Aihua Wang (Veterinary Microbiology, 2026)

UiO-66 porous liquids with synergistic catalytic effects for promoting efficient CO2 conversion - Yaru Lu; Ruyu Bai; Dechao Wang; Yangyang Xin; Weirui Zhang; Fangfang Su; Zheng Dong; Wendi Fan; Yating Zhang; Fangli Yu; Xin Li; Yingying Zhou; et al. (Chemical Engineering Journal, 2026)

Long-term fertilization-induced increases in glomalin-related soil protein depend on phosphorus input and aggregate stability across climatic zones - Hongbo Yang; Guanmo Li; Dong Wu; Qiong Xiao; Xin Li; Yaping Huang; Jeroen Meersmans; Gilles Colinet; Minggang Xu; Wenju Zhang (Soil and Tillage Research, 2026)

Composition, Distribution and Constraining Factors of Fe Isotope (δ56Fe) in the Surface Soils of the Tibetan Plateau - Ting Wei; Zhiwen Dong; Eric Parteli; Xiaoli Liu; Shichang Kang; Yaping Shao (Journal of Earth Science, 2026)

Spatial Distribution and Release Flux of Carbon and Nitrogen Components in Glacial Watersheds of Eastern Tibetan Plateau - Xiaoyu Jiao; Zhiwen Dong; Xiang Qin; Xiaoxiang Wang; Yaping Shao (Journal of Earth Science, 2026)

Removal performance, molecular characteristics, and microbial mechanisms of dissolved organic nitrogen from secondary effluent in a pyrite-based autotrophic denitrification constructed wetland - Dong Wei; Yaping Sun; Xinwen Zhang; Shouqing Ni (Water Research, 2026)

Zn isotopic composition and variability in large-scale aquatic environment of the Tibetan Plateau: implications for Zn migration and sources - Xiaoli Liu; Zhiwen Dong; Yan Yan; Rui Wu; Lunche Wang; Yaping Shao (Journal of Hydrology, 2026)

Interface layer-assisted construction of metal organic framework based porous liquids for high performance CO2 selective separation - Zheng Dong; Yangyang Xin; Bowen Xiang; Ruilu Yang; Menglin Zhu; Baolu Cui; Chenjiao Xie; Shuangshuang Long; Wenwu Zhou; Jianwei Liu; Libing Qian; Hongze Guo; et al. (Journal of Environmental Chemical Engineering, 2025)

Highly sensitive and wide-range quantification of bovine αS1-casein in foods for predicting potential milk allergenicity using an IgE multi-epitope-specific antibody - Caiyi Shen; Liming Li; Caiyun Long; Yunbiao Luo; Yaping Dong; Jinyu Yu; Yi Yao; Guanrong Hu; Xin Li; Hongbing Chen; Shengfa He (Food Chemistry, 2025)

Anti-inflammatory Effects of Membrane Vesicles from Eubacterium rectale via the NLRP3 Signal Pathway - Hongxia Zhang; Yanan Zhao; Dengfu Li; Haixia Li; Zhu Wang; Lu Zhang; Huafeng Niu; Yuchen Huang; Chenchong Zhao; Yaping Jin; Dong Zhou (Probiotics and Antimicrobial Proteins, 2025)

Transcription factor OxyR regulates peroxidase levels to enhance Brucella's defense against oxidative stress - Yunyi Zhai; Hui Wang; Guangdong Zhang; Bin Li; Ziyang Diao; Lei Chen; Lulu Tian; Feijie Zhi; Junmei Li; Dong Zhou; Wei Liu; Yaping Jin; et al. (Veterinary Microbiology, 2025)

U-Li Isotopes highlight the dominant role of glacier coverage in weathering processes across Northeast Tibetan Plateau glacial watersheds - Xiaoyu Jiao; Zhiwen Dong; Giovanni Baccolo; Xiang Qin; Yaping Shao (Global and Planetary Change, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

MoS2 QDs-decorated mesoporous polydopamine nanoparticle as a GSH responsive peroxidase-like nanozyme for effective antibacterial therapy - Kayi Shao; Linlong Zhang; Yaping Zhong; Dong Wang (Chemical Engineering Journal, 2025)

Mutation in maize chloroplastic polypeptide chain release factor (ZmcpRF1) affects chloroplast development and leaf color - Hao Chen; Haixiao Dong; Xiaohui Shan; Yuan Jiang; Shipeng Li; Hongkui Liu; Shengzhong Su; Yaping Yuan (Planta, 2025)

Integrated coordination of production scheduling, preventive maintenance, and energy conservation in flexible manufacturing environments - Yu Wang; Tangbin Xia; Yaping Li; Shuo Gao; Dong Wang; Lifeng Xi (Journal of Cleaner Production, 2025)

Glyphosate exposure impairs glucose and lipid metabolism by disturbing the circadian clock system in mice liver - Bonan Xiao; Haizhen Jiang; Hao Dong; Chao Li; Haisen Zhang; Dengke Gao; Aihua Wang; Yaping Jin; Huatao Chen (Food and Chemical Toxicology, 2025)

Corrigendum to “Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption” [Chem. Eng. J. 500 (2024) 156655] - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2025)

The effect of removing bound polyphenols on the physicochemical and functional properties of Rosa roxburghii tratt dietary fiber in vitro - Xiaoli Zhou; Zhicheng Qin; Yan Chen; Yaping Wang; Dong Lin; Lingshuai Meng (Food Bioscience, 2025)

Current research on the medical importance of Trametes species - Rathna Silviya Lodi; Xiaodan Dong; Xinkun Wang; Yaping Han; Xiaohui Liang; Chune Peng; Lizeng Peng (Fungal Biology Reviews, 2025)

Dynamic simulation of local acceptance of NIMBY facilities based on the RAS-Deffuant model: The influence of government and media information - Xin Wan; Rubing Wang; Xiaoyu Dong; Jiayue Wu; Yaping Zheng; Qian Li (Environmental Impact Assessment Review, 2025)

Polyanionic hydrogel electrolytes applied to interface-stabilized zinc ion hybrid capacitors - Pengyun Xie; Xin Wang; Yaping Jiang; Ying Tang; Kaifa Dong; Hui Peng; Guofu Ma; Ziqiang Lei (Chemical Engineering Journal, 2025)

Boosting electrocatalytic performance of BaPrO3-δ −based cathode catalysts by Co and Ni co-doping for protonic ceramic fuel cells - Bo Liu; Yanping Zheng; Xinwei Yang; Yaping Liu; Dong Yan; Jian Li; Lichao Jia (Chemical Engineering Journal, 2025)

Bioactive polysaccharides from Momordica charantia as functional ingredients: a review of their extraction, bioactivities, structural-activity relationships, and application prospects - Jiamei Zheng; Mingyue Shang; Guona Dai; Jingjing Dong; Yaping Wang; Baozhong Duan (Critical Reviews in Food Science and Nutrition, 2024)

The alleviating effects and mechanisms of Lactiplantibacillus plantarum MC14 on hyperuricemia in mice - Jie Xiong; Jia-Juan Wu; Dong-mei Liu; Muhammad Yousaf; Liu-Jun Liu; Suping Zeng; Qinqin Li; Jun Tang; Yaping Wu (Food Bioscience, 2024)

Porous liquids based on UiO-66@SiO2 through the strategy of growing an ultrathin silica layer for CO2 selective separation - Zhaodi Wang; Yangyang Xin; Wendi Fan; Zheng Dong; Dechao Wang; Yaping Zheng; Yahong Xu (Chemical Engineering Journal, 2024)

Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2024)

Assessment of uric acid-lowering activity, safety and stress tolerance of Lactiplantibacillus plantarum MC14 based on whole gene sequencing and phenotyping experiments - Jie Xiong; Lingxing Feng; Muhammad Yousaf; Suping Zeng; Jun Tang; Yaping Wu; Qinqin Li; Dong-mei Liu (Food Bioscience, 2024)

Recalcitrant components accumulation in dissolved organic matter decreases microbial metabolic quotient of red soil under long-term manuring - Xiao Yang; Shuai Zhang; Dong Wu; Yaping Huang; Lu Zhang; Kailou Liu; Huiqiao Wu; Shengli Guo; Wenju Zhang (Science of The Total Environment, 2024)

Effect of complex prebiotics on Lactobacillus gasseri JM1 fermented soymilk: Physicochemical, flavor characteristics, and metabolites - Yaping Zheng; Wenfang Wu; Man Zhu; Yilin Sun; Dong Hu; Yujun Jiang; Yu Zhang; Chaoxin Man (Food Bioscience, 2024)

Distribution and source of heavy metals in Tibetan Plateau topsoil: New insight into the influence of long-range transported sources to the surrounding glaciers - Xiaoli Liu; Wenhua Gao; Ting Wei; Zhiwen Dong; Jiawen Ren; Yaping Shao; Xuejiao Chen (Environmental Pollution, 2024)

Relationship of environmental exposure temperature and temperature extremes on sperm DNA fragmentation index in men with different BMI values and the indirect effect of DNA fragmentation index on semen parameters - Chen Wang; Qiwei Yu; Ting Chu; Fang Wang; Fangli Dong; Hang Xin; Di Wang; Yaping Liu; Jun Zhai (Science of The Total Environment, 2024)

On-site smartphone detection of ethanol content using paper-based colorimetric polydiacetylene sensor arrays - Dong-En Wang; Changhan Yan; Sirui Bai; Yaping Zhang; Wenjing Huo; Kaiting Ning; Lei Zhao; Hui Yang; Huiyun Xu (Chemical Engineering Journal, 2024)

Composition and constraints of lithium isotopes in cryoconite from various remote glacier areas of the Tibetan Plateau - Jie Di; Zhiwen Dong; Yaping Shao; Xiaoyu Jiao; Ting Wei (Science of The Total Environment, 2024)

Quantifying uranium radio-isotope ratios in riverine suspended particulate matter: Insights into natural and anthropogenic influences in the glacial-fed river system of the NE Tibetan Plateau - Xiaoyu Jiao; Zhiwen Dong; Giovanni Baccolo; Xiang Qin; Ting Wei; Jie Di; Yaping Shao (Journal of Hazardous Materials, 2024)

pH is the major predictor of soil microbial network complexity in Chinese forests along a latitudinal gradient - Dorsaf Kerfahi; Yaping Guo; Ke Dong; Qingkui Wang; Jonathan M. Adams (CATENA, 2024)

Integrated scheduling problems of open shop and vehicle routing using an ensemble of group teaching optimization and simulated annealing - Jiaming Su; Yaping Fu; Kaizhou Gao; Hongyu Dong; Jianhui Mou (Swarm and Evolutionary Computation, 2023)

Clean removal of silicon (IV) and vanadium (V) from high concentration chromium (VI) solutions in the chromate production processes - Xinqian Li; Bo Li; Yaping Dong; Zhengrong Niu; Dandan Gao; Haitao Feng; Wu Li (Journal of Cleaner Production, 2023)

Proteomic analysis of uterine lavage fluid of dairy cows at different time after delivery by mass spectrometry - Xingcan Jiang; Ziyuan Li; Xiyu Chang; Cong Huang; Rendong Qiu; Aihua Wang; Pengfei Lin; Keqiong Tang; Huatao Chen; Dong Zhou; Yaping Jin (Theriogenology, 2023)

Sodium acetate trihydrate/melamine foam composite PCM encapsulated by CuS/rGO modified epoxy resin and endowed with light-to-heat conversion properties - Henghua Zhang; Qianbin Dong; Yaping Tang; Jialing Wu; Wenjian Bi; Yue Gao; Jiabang Wang; Hui Yang (Chemical Engineering Journal, 2023)

Origin, composition, and accumulation of dissolved organic matter in a hypersaline lake of the Qinghai-Tibet Plateau - Yaoling Zhang; Keli Yang; Hongmei Chen; Yaping Dong; Wu Li (Science of The Total Environment, 2023)

Carbon emission model of vehicles driving at fluctuating speed on highway - Yaping Dong; Jinliang Xu; Jie Ni (Environmental Science and Pollution Research, 2022)

Transcriptome Analysis Reveals Differential Gene Expression in Garlic Aerial Bulbs in Response to Gibberellin Application - Yuhui Dong; Hongcheng Fang; Yujiao Hou; Yaping Zhao; Xiudong Sun; Shiqi Liu (Journal of Plant Growth Regulation, 2022)

Development of center pivot irrigation farmlands from 2009 to 2018 in the Mu Us dune field, China: Implication for land use planning - Xiaokang Liu; Zhibao Dong; Yaping Ding; Ruijie Lu; Liyun Liu; Zhiyong Ding; Yijing Li (Journal of Geographical Sciences, 2022)

Regulation of wound healing and fibrosis by galectins - Dong Yu; Ming Bu; Ping Yu; Yaping Li; Yang Chong (Journal of Molecular Medicine, 2022)

BMAL1 induces colorectal cancer metastasis by stimulating exosome secretion - Pengjuan Dong; Yaping Wang; Yutong Liu; Chunting Zhu; Jiaxin Lin; Ruizhe Qian; Luchun Hua; Chao Lu (Molecular Biology Reports, 2022)

Chemical composition and Pb(II) binding of dissolved organic matter in a hypersaline lake in China - Keli Yang; Yaoling Zhang; Yaping Dong; Wu Li (Journal of Oceanology and Limnology, 2022)

Trueperella pyogenes pyolysin inhibits lipopolysaccharide-induced inflammatory response in endometrium stromal cells via autophagy- and ATF6-dependent mechanism - Maozhen Qi; Jianguo Liu; Qingran Jiang; Hongyu Niu; Xinyu Wang; Dong Zhou; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin (Brazilian Journal of Microbiology, 2021)

Decreased grain size1, a C3HC4-type RING protein, influences grain size in rice (Oryza sativa L.) - Xingjie Zhu; Shengzhong Zhang; Yaping Chen; Changlin Mou; Yunshuai Huang; Xi Liu; Jingli Ji; Jiangfeng Yu; Qixian Hao; Chunyan Yang; Mengying Cai; Thanhliem Nguyen; et al. (Plant Molecular Biology, 2021)

Conditional Deletion of Foxg1 Alleviates Demyelination and Facilitates Remyelination via the Wnt Signaling Pathway in Cuprizone-Induced Demyelinated Mice - Fuxing Dong; Dajin Liu; Feiyu Jiang; Yaping Liu; Xiuxiang Wu; Xuebin Qu; Jing Liu; Yan Chen; Hongbin Fan; Ruiqin Yao (Neuroscience Bulletin, 2021)
The massive loss of oligodendrocytes caused by various pathological factors is a basic feature of many demyelinating diseases of the central nervous system (CNS). Based on a variety of studies, it is now well established that impairment of oligodendrocyte precursor cells (OPCs) to differentiate and remyelinate axons is a vital event in the failed treatment of demyelinating diseases. Recent evidence suggests that Foxg1 is essential for the proliferation of certain precursors and inhibits premature neurogenesis during brain development. To date, very little attention has been paid to the role of Foxg1 in the proliferation and differentiation of OPCs in demyelinating diseases of the CNS. Here, for the first time, we examined the effects of Foxg1 on demyelination and remyelination in the brain using a cuprizone (CPZ)-induced mouse model. In this work, 7-week-old Foxg1 conditional knockout and wild-type (WT) mice were fed a diet containing 0.2% CPZ w/w for 5 weeks, after which CPZ was withdrawn to enable remyelination. Our results demonstrated that, compared with WT mice, Foxg1 -knockout mice exhibited not only alleviated demyelination but also accelerated remyelination of the demyelinated corpus callosum. Furthermore, we found that Foxg1 knockout decreased the proliferation of OPCs and accelerated their differentiation into mature oligodendrocytes both in vivo and in vitro . Wnt signaling plays a critical role in development and in a variety of diseases. GSK-3β, a key regulatory kinase in the Wnt pathway, regulates the ability of β-catenin to enter nuclei, where it activates the expression of Wnt target genes. We then used SB216763, a selective inhibitor of GSK-3β activity, to further demonstrate the regulatory mechanism by which Foxg1 affects OPCs in vitro . The results showed that SB216763 clearly inhibited the expression of GSK-3β, which abolished the effect of the proliferation and differentiation of OPCs caused by the knockdown of Foxg1 . These results suggest that Foxg1 is involved in the proliferation and differentiation of OPCs through the Wnt signaling pathway. The present experimental results are some of the first to suggest that Foxg1 is a new therapeutic target for the treatment of demyelinating diseases of the CNS.

Transcriptomic analysis reveals somatic embryogenesis-associated signaling pathways and gene expression regulation in maize (Zea mays L.) - Meiqi Ding; Haixiao Dong; Yingjie Xue; Shengzhong Su; Ying Wu; Shipeng Li; Hongkui Liu; He Li; Junyou Han; Xiaohui Shan; Yaping Yuan (Plant Molecular Biology, 2020)

Generation of mice with hepatocyte-specific conditional deletion of sphingosine kinase 1 - Jinfeng Yu; Jiale Dong; Kangdi Chen; Yaping Ding; Zhicheng Yang; Tian Lan (Transgenic Research, 2020)

Simulation of Yesso scallop, Patinopecten yessoensis, growth with a dynamic energy budget (DEB) model in the mariculture area of Zhangzidao Island - Weiwei Jiang; Fan Lin; Meirong Du; Jianguang Fang; Jinghui Fang; Yaping Gao; Xiaoqin Wang; Fengxue Li; Shipeng Dong; Xing Hou; Zengjie Jiang (Aquaculture International, 2020)

Brittleness index analysis of coal samples - Haibo Wu; Pingsong Zhang; Shouhua Dong; Yaping Huang; Min Zhang (Acta Geophysica, 2019)

Comparative genomics for non-O1/O139 Vibrio cholerae isolates recovered from the Yangtze River Estuary versus V. cholerae representative isolates from serogroup O1 - Li Gong; Pan Yu; Huajun Zheng; Wenyi Gu; Wei He; Yadong Tang; Yaping Wang; Yue Dong; Xu Peng; Qunxin She; Lu Xie; Lanming Chen (Molecular Genetics and Genomics, 2019)

Chemical characterization of fractions of dissolved humic substances from a marginal sea—a case from the Southern Yellow Sea - Yaoling Zhang; Keli Yang; Jinzhou Du; Fenfen Zhang; Yaping Dong; Wu Li (Journal of Oceanology and Limnology, 2018)

Evaluation of CBM reservoir fracture characteristics by azimuthal AVA inversion - Yiming Zhuang; Shouhua Dong; Haibo Wu; Yaping Huang (Arabian Journal of Geosciences, 2017)

Autoantibody to MOG suggests two distinct clinical subtypes of NMOSD - Yaping Yan; Yujing Li; Ying Fu; Li Yang; Lei Su; Kaibin Shi; Minshu Li; Qiang Liu; Aimee Borazanci; Yaou Liu; Yong He; Jeffrey L. Bennett; et al. (Science China Life Sciences, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Fingolimod alters inflammatory mediators and vascular permeability in intracerebral hemorrhage - Yu-Jing Li; Guo-Qiang Chang; Yuanchu Liu; Ye Gong; Chunsheng Yang; Kristofer Wood; Fu-Dong Shi; Ying Fu; Yaping Yan (Neuroscience Bulletin, 2015)

Removal of Trace As(V) from Water with the Titanium Dioxide/ACF Composite Electrode - Liang Peng; Yaping Chen; Hong Dong; Qingru Zeng; Huijuan Song; Liyuan Chai; Ji-dong Gu (Water, Air, & Soil Pollution, 2015)

Alterations of natural killer cells in traumatic brain injury - Xiao-Dong Kong; Sheng Bai; Xin Chen; Hui-Jie Wei; Wei-Na Jin; Min-Shu Li; Yaping Yan; Fu-Dong Shi (Neuroscience Bulletin, 2014)

Effect of chlorogenic acid on LPS-induced proinflammatory signaling in hepatic stellate cells - Haitao Shi; Lei Dong; Xiaoyan Dang; Yaping Liu; Jiong Jiang; Yan Wang; Xiaolan Lu; Xiaoyan Guo (Inflammation Research, 2013)

Construction and Characterization of Two Bacterial Artificial Chromosome Libraries of Grass Carp - Songhun Jang; Hang Liu; Jianguo Su; Feng Dong; Feng Xiong; Lanjie Liao; Yaping Wang; Zuoyan Zhu (Marine Biotechnology, 2010)

Generation and analysis of expressed sequence tags from the medicinal plant Salvia miltiorrhiza - YaPing Yan; ZheZhi Wang; Wei Tian; ZhongMin Dong; David F. Spencer (Science China Life Sciences, 2010)

Ordovician limestone aquosity prediction using nonlinear seismic attributes: Case from the Xutuan coal mine - Yaping Huang; Shouhua Dong; Jianhua Geng (Applied Geophysics, 2009)

A quick isolation method for mutants with high lipid yield in oleaginous yeast - Jufang Wang; Renmin Li; Dong Lu; Shuang Ma; Yaping Yan; Wenjian Li (World Journal of Microbiology and Biotechnology, 2009)